Dual Band Antenna for satellite Communication - Roy, K; Pal, S; Sinha, A; Roy, B; Billaha, M.A; Mondal, B; Chakraborty, S; Ranjan, P (International Journal of Computer Sciences and Engineering, 2025)
This paper describes the design and analysis of a novel dual band antenna (with a Rogers RT/Duroid 6202 laminate substrate having dielectric constant 4.4) for satellite communication. The antenna is being designed by taking the substrate height as 1.6 mm, the length of the patch as 27.5 mm and the width of the patch as 38 mm. The length and width for slot 1 and slot 2 were taken as 33 mm and 2.4 mm respectively. Similarly the length and width of slot 3 and slot 4 were considered as 11.4 mm and 1mm. We have considered the feed point location as (8.6, 8.6) from the origin. The simulation results of proposed antenna are achieved with the help of IE3D zeland software (V-12.0) using transmission line and cavity models. The results are analyzed in terms of current distribution, elevation pattern, return loss and voltage standing wave ratio (VSWR). This antenna finds C band (4 GHz to 8 GHz) and X band (8 to 12 GHz) applications where it can be effectively used for satellite communication.